Site Preferences of Copper and Cobalt Monobenzo Porphyrins in a Trans-Dibenzo Adsorption Structure on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto dos Santos, Alisson; Gazetas, Lampros-Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Steinrück, Hans-Peter; Lytken, Ole (ChemPhysChem, 2025)
Using scanning tunneling microscopy, Cu and Co tetraphenyl monobenzo porphyrins are used as probe molecules to better understand the T-type interactions within well-ordered islands of Cu and Co tetraphenyl trans-dibenzo porphyrins on Cu(111). The islands are made up of molecular rows, held together by T-type interactions between isoindole and phenyl rings of adjacent molecules. The monobenzo molecules are found to be depleted within the bulk of the molecular rows and enriched at the edges terminating the rows. By counting over 50 000 molecules and using equilibrium considerations, the T-type interaction energies within the trans-dibenzo islands are estimated and the derived values are compared to values previously calculated with density functional theory, which find very good agreement for Cu-TPtdBP but less satisfying agreement for Co-TPtdBP.
CRIS-Team Scopus Importer:2025-11-07
Keywords: Cu(111); porphyrins; scanning tunneling microscopy; statistical analysis; T-type interaction